2016
DOI: 10.1016/j.ijpam.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Bullying in early adolescence

Abstract: Background and objectivesThis study aimed to gain a deeper understanding of bullying among intermediate school students in Saudi Arabia to inform preventive measures.Materials and methodsQualitative methods were applied. The study was conducted at four intermediate schools. Students, parents, and school professionals participated, and data were collected through observations, interviews, and focus groups. Emergent themes and subthemes were identified through coding.ResultsA total of 91 individuals participated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…In this study, the prevalence of being bullied was more than triple the one reported in a health survey conducted on Saudi adolescents, 2014 (Al Buhairan et al, 2016). Our study was conducted on younger children who usually are naive and sincere in their reporting of events, while older students might get ashamed if they are bullied so they under-report their events (Napolitano, 2011).…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…In this study, the prevalence of being bullied was more than triple the one reported in a health survey conducted on Saudi adolescents, 2014 (Al Buhairan et al, 2016). Our study was conducted on younger children who usually are naive and sincere in their reporting of events, while older students might get ashamed if they are bullied so they under-report their events (Napolitano, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…The Peer Interaction in Primary School Questionnaire designed by Tarshis and Huffman and Adolescent Peer Relations Instrument by Parada, R. are used to build the study questionnaire. (Tarshis, 2007;Al Buhairan et al, 2016).…”
Section: Data Collection Toolmentioning
confidence: 99%
See 1 more Smart Citation
“…Only 7% of U.S. parents are worried about cyberbullying, even though 33% of teenagers have been victims of cyberbullying. 18% of 8 to 10-year-olds spend time on some kind of social networking site daily [10][11][12][13][14].…”
Section: School Bulling In Saudi Arabiamentioning
confidence: 99%
“…Prevalence estimates in these countries ranged from 20.9% to 44.2%. In Saudi Arabia, AlBuhairan et al [14] explored the topic in the capital city (Riyadh) and reported that all forms of bullying (verbal, physical, sexual, psychological/social, and cyberbullying) were present in the Saudi community. Cyberbullying is a new form of bullying where the aggressive or intentional act is carried out repeatedly and over time by a group or individual, using electronic forms of contact, mainly through phones and the internet, against a victim who cannot easily defend against it [15].…”
mentioning
confidence: 99%